1.39 Ga mafic dyke swarm in southwestern Yilgarn Craton marks Nuna to Rodinia transition in the West Australian Craton - Stark, J. Camilla; Wang, X.; Li, Zheng-Xiang; Denyszyn, S.; Rasmussen, Birger; Zi, Jianwei (Elsevier BV, 2018)
The Archean Yilgarn Craton in Western Australia hosts at least five generations of mafic dykes ranging from Archean to Neoproterozoic in age, including the craton-wide ca. 2408 Ma Widgiemooltha and the 1210 Ma Marnda Moorn Large Igneous Provinces (LIP), the 1888 Ma Boonadgin dykes in the southwest and the 1075 Ma Warakurna LIP in the northern part of the craton. We report here a newly identified NNW-trending mafic dyke swarm, here named the Biberkine dyke swarm, in the southwestern Yilgarn Craton dated at 1390 ± 3 Ma by ID-TIMS U-Pb geochronology of baddeleyite. The regional extent of the dyke swarm is uncertain but aeromagnetic data suggest that the dykes are part of a linear swarm several hundred kilometers long, truncated by the Mesoproterozoic Albany-Fraser Orogen to the south. Geochemical data indicate that the dykes have tholeiitic compositions with a significant contribution from metasomatically enriched subcontinental lithospheric mantle and/or lower continental crust. Paleogeographic reconstructions suggest that a prolonged tectonic quiescence in the Yilgarn Craton from ca. 1600 Ma was interrupted by renewed subduction along the southern and southeastern margin at ca. 1400 Ma, reflecting a transition from Nuna to Rodinia configuration. The 1390 Ma Biberkine dykes may be a direct consequence of this transition and mark the change from a passive to active tectonic setting, which culminated in the Albany-Fraser Orogeny at ca. 1330 Ma. The Biberkine dykes are coeval with a number of other mafic dyke swarms worldwide and provide an important target for paleomagnetic studies.